Stylistic Features to Reveal Undergraduates’ Writing Style - Muhammad Alif Rizkiawan; Dian Safitri (Universitas Negeri Padang, 2023)
Narrative writing serves both educational and creative goals, such as in character-driven stories. This article is a conceptual article to come up with Rubin & Greene (1992) coded-stylistic features in the way to investigate the relation of writing styles across the genders. Writing style develops with time, especially in character-based fiction, encouraging the growth of unique traits important to fostering cultural sensitivity and civic engagement. Understanding gender norms in society helps to shape students' educational opportunities. Academic achievement, classroom dynamics, pedagogical decisions, and learning outcomes are all influenced by gender stereotypes. The societal character of language is shown by Argamon et al. (2003), who emphasize the effect of gender on lexical choice and speech patterns. Character-focused schooling, in particular, can benefit from this interplay between gender and writing style by encouraging the development of individual traits that have broader cultural significance.